KEEFEKTIFAN MEDIA E-KOMIK BERBASIS STEM MATERI ENERGI ALTERNATIF UNTUK MENINGKATKAN LITERASI SAINS DAN LITERASI DIGITAL SISWA SEKOLAH DASAR - Muhammad Nur Ikhsan; Bambang Subali; Ellianawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the effectiveness of STEM-based e-comic media in teaching alternative energy topics to enhance scientific literacy and digital literacy among elementary school students. A mixed-methods approach was employed, using a pretest-posttest control group design. The sample consisted of 140 fourth-grade students, divided into experimental and control groups. Data collection instruments included scientific and digital literacy tests, student response questionnaires, observation sheets, and interview guidelines. N-Gain analysis revealed a more significant improvement in the experimental group (moderate category) compared to the control group (low category). T-test results indicated a statistically significant difference between pretest and posttest scores, both within the experimental group and between the experimental and control groups. Qualitative data showed that students responded positively to the e-comic media, found it helpful in understanding alternative energy concepts, and were engaged by its visually appealing design. These findings demonstrate that STEM-based e-comic is an effective learning medium to improve elementary student’s scientific and digital literacy.